Menakar Efektivitas Hukum Lingkungan dalam Mewujudkan Pariwisata Berkelanjutan: Studi Kasus Kawasan Wisata Mandalika - Ni Luh Ariningsih Sari; Titin Apriani (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The development of the Mandalika Special Economic Zone (SEZ) as one of Indonesia’s priority tourism destinations has significantly contributed to national economic growth through increased investment and rapid infrastructure development. However, this accelerated expansion has also created substantial environmental pressures, particularly on coastal ecosystems, including increased waste generation, degradation of marine habitats, and changes in land use patterns. This study aims to analyze the role of environmental law in promoting sustainable tourism in the Mandalika area by examining the effectiveness of regulatory instruments and their implementation in practice. Using a qualitative research approach employing in-depth interviews, field observations, and policy document analysis this study finds that although a regulatory framework for environmental protection is in place, its implementation faces several challenges, such as weak enforcement, limited transparency of environmental documents, and low levels of community participation in the Environmental Impact Assessment (EIA) process. The findings highlight the need to strengthen environmental governance through enhanced multi-stakeholder collaboration, integration of local wisdom, and the adoption of sustainable tourism standards. This research provides practical contributions for policymakers in formulating more effective environmental management strategies to ensure the long-term sustainability of Mandalika as a leading tourism destination.